2012
DOI: 10.1080/17290376.2012.745639
|View full text |Cite
|
Sign up to set email alerts
|

Kwazulu-Natal minibus taxi drivers' perceptions on HIV and AIDS: Transmission, prevention, support and effects on the industry

Abstract: In South Africa, the minibus taxi drivers are largely becoming another high-risk category in the HIV and AIDS epidemic. Although previous studies have shown that knowledge of HIV and AIDS is relatively high among the taxi drivers it is still not clear how this sub-population perceive the support rendered to them with regard to HIV and AIDS prevention strategies. This study aimed to focus on this atypical workplace and explore the KwaZulu-Natal, minibus taxi drivers' perceptions on HIV and AIDS. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The findings of the earlier phases have been reported in previous publications. 7,8 This article reports on the qualitative section of the study, which was gathered over the period of 2013 to 2015. The aim of the qualitative section of the main study was to explore condom use and strategies that inform condom use negotiations among the minibus taxi drivers' and the taxi queens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the earlier phases have been reported in previous publications. 7,8 This article reports on the qualitative section of the study, which was gathered over the period of 2013 to 2015. The aim of the qualitative section of the main study was to explore condom use and strategies that inform condom use negotiations among the minibus taxi drivers' and the taxi queens.…”
Section: Methodsmentioning
confidence: 99%
“…6 Relevant research findings have indicated that a substantial proportion of minibus taxi drivers engage in risky sex but seldom considered themselves to be at risk of STIs or HIV/AIDS. 6,7,8 With such risky sexual behaviours, links have been made between minibus taxi drivers' sexual relationship and so-called taxi queens, whereby young and impoverished women engage in transactional and intergenerational relationships. 9,10 HIV transmission has been linked in particular to concurrent relationships and intergenerational sex (age mixing in sex).…”
Section: Introductionmentioning
confidence: 99%
“…The most convenient time to approach the taxis was between 9 am and 12 pm. 18 The questionnaire was self-administered, or researcher-administered should the participant request to be assisted. The study was quantitative in nature using a semi-structured questionnaire derived from WHO (the questionnaire is available as Supplementary data at JAC-AMR Online).…”
Section: Methodsmentioning
confidence: 99%
“…The taxi industry is predominantly male, with operators who are aged between 25 and 44 years. 18 The taxi operators receive their remuneration on a quarterly basis or as a fixed amount per day based on daily targets that are agreed upon between taxi operator and taxi owner. 19 These daily targets have resulted in long working hours, causing increased stress levels, unhealthy diet, lack of exercise, smoking and consumption of alcohol and stimulants, which all have contributed to operators having various chronic and acute illnesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation